Infinite order differential equations in the space of entire functions of normal type with respect to a proximate order - Ishimura , Ryuichi; Jin, Xiaoran (North-Western European Journal of Mathematics, 2019)
In this paper, we consider the space of entire functions with normal type growth for a given proximate order and a continuous linear operator from such space into itself which is defined by a partial differential operator of infinite order. We will study corresponding partial differential equations with variable coefficients in the cases of regular singular type and of Korobeı̆nik type.